Hypothermia for perinatal asphyxia: trial-based quality of life at 6–7 years. Issue 7 (6th March 2018) - Campbell, Helen; Eddama, Oya; Azzopardi, Denis; Edwards, A David; Strohm, Brenda; Rivero-Arias, Oliver
Abstract : Objective: To assess the impact of hypothermic neural rescue at birth on health-related quality of life (HRQL) in middle childhood. Design: Six-year to 7-year follow-up of surviving children from the Total Body Hypothermia for Neonatal Encephalopathy (TOBY) Trial. Setting: Community study including a single parental questionnaire to collect information on children's HRQL. Patients: 145 children (70 in the control group, 75 in the hypothermia group) whose parents consented and returned the questionnaire. Interventions: Intensive care with cooling of the body to 33.5°C for 72 hours or intensive care alone. Main outcome measures: HRQL attributes and utility scores using the Health Utilities Index (HUI). Results: At 6–7 years, speech appeared disproportionately affected when compared with other aspects of HRQL but levels of normal emotional functioning were similar in both groups. The mean (SE) HUI3 HRQL scores were 0.73 (0.05) in the hypothermia group and 0.62 (0.06) in the control group; mean difference (95% CI) 0.11 (−0.04 to 0.26). Conclusions: Findings of non-significant differences were not unexpected; the study used data from long-term survivors in a neonatal trial and was underpowered. However, results favoured moderate hypothermia and so complement the clinical results of the TOBY Children study. The work provides further insight into the long-term HRQL impact of perinatal asphyxial encephalopathy and provides previously unavailable utility data with which to contemplate the longer term cost-effectiveness of hypothermic neural rescue. Trial registration number: This study reports on the follow-up of the TOBY clinical trial: ClinicalTrials.gov number NCT01092637 .